Pengembangan media video internalisasi nilai-nilai akhlak mahasiswa berbasis teoantropoekosentris di UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan - Al-Husna, Khofifah Indah; Magdalena, Magdalena; Daulay, Muhammad Roihan (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2025)
This study aims to develop a video media for internalizing students' moral values ​​based on theoanthropopoecocentric at UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, using the ADDIE research model (Analysis, Design, Development, Implementation, Evaluation). The results show that the analysis of student needs really likes videos in the form of live dialogues, videos taken around the dormitory, using Indonesian, duration less than 10-15 minutes, using additional text and musical accompaniment. The scene contains morals of mutual respect, responsibility and fairness with an introduction to the campus at the beginning of the video. The design of the video media starts from determining the flow, preparing the material in the video, then continuing with development based on the assessment of media and material experts. The results of the implementation and evaluation of the video media are that students can easily understand the video and its objectives and are very inspired and touched so that they feel interested in internalizing the concept of theoanthropopoecocentric, providing a deeper understanding of living life and students realize the importance of morals that are not only oriented towards themselves.